PERAN GURU EKSTRAKURIKULER DALAM PEMBINAAN DAN PENINGKATAN KOMPETENSI BAHASA ARAB PESERTA DIDIK DI MAN 1 KOTA PADANG - Amal Syahidin; Sanra Mahenra Hatoguan; Fuji Arifzapni; Ardi Rambe (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the role of extracurricular teachers in improving students’ Arabic proficiency at MAN 1 Padang. Arabic proficiency in this study includes listening, speaking, reading, and writing skills, as well as mastery of mufradat and qawaid. This research employed a qualitative approach using a descriptive method. The research subjects consisted of Arabic extracurricular teachers and students participating in the program. Data were collected through observation, interviews, and documentation. The findings show that extracurricular teachers play important roles as facilitators, motivators, and mentors in creating an active and enjoyable learning atmosphere. Teachers also applied various strategies, such as conversation practice, Arabic language games, group discussions, and enrichment materials outside formal class hours. In addition, teachers provided individual guidance for students experiencing learning difficulties. The main obstacles included differences in students’ abilities and limited activity time. However, through effective management, extracurricular activities gradually improved students’ interest, self-confidence, and Arabic proficiency. These improvements were reflected in greater participation, stronger communication confidence, and better understanding of learning materials throughout the process.